Molecular mechanisms behind progressing chronic inflammatory dilated cardiomyopathy - Bironaité, Daiva; Labeit, Siegfried (BMC cardiovascular disorders, 2015)
Background: Inflammatory dilated cardiomyopathy (iDCM) is a common debilitating disease with poor prognosis that often leads to heart failure and may require heart transplantation. The aim of this study was to evaluate sera and biopsy samples from chronic iDCM patients, and to investigate molecular mechanism associated with left ventricular remodeling and disease progression in order to improve therapeutic intervention. Methods: Patients were divided into inflammatory and non-inflammatory DCM groups according to the immunohistochemical expression of inflammatory infiltrates markers: T-lymphocytes (CD3), active-memory T lymphocyte (CD45Ro) and macrophages (CD68). The inflammation, apoptosis, necrosis and fibrosis were investigated by ELISA, chemiluminescent, immunohistochemical and histological assays. Results: The pro-inflammatory cytokine IL-6 was significantly elevated in iDCM sera (3.3 vs. 10.98 μg/ml; P < 0.05). Sera levels of caspase-9, -8 and -3 had increased 6.24-, 3.1- and 3.62-fold, (P < 0.05) and only slightly (1.3-, 1.22- and 1.03-fold) in biopsies. Significant release of Hsp60 in sera (0.0419 vs. 0.36 ng/mg protein; P < 0.05) suggested a mechanistic involvement of mitochondria in cardiomyocyte apoptosis. The significant MMP9/TIMP1 upregulation in biopsies (0.1931 - 0.476, P < 0.05) and correlation with apoptosis markers show its involvement in initiation of cell death and ECM degradation. A slight activation of the extrinsic apoptotic pathway and the release of hsTnT might support the progression of chronic iDCM. Conclusions: Data of this study show that significant increase of IL-6, MMP9/TIMP1 and caspases-9, -8, -3 in sera corresponds to molecular mechanisms dominating in chronic iDCM myocardium. The initial apoptotic pathway was more activated by the intramyocardial inflammation and might be associated with extrinsic apoptotic pathway through the pro-apoptotic Bax. The activated intrinsic form of myocardial apoptosis, absence of necrosis and decreased fibrosis are most typical characteristics of chronic iDCM. Clinical use of anti-inflammatory drugs together with specific anti-apoptotic treatment might improve the efficiency of therapies against chronic iDCM before heart failure occurs.